PEMBERIAN BEBERAPA DOSIS PUPUK NPK TERHADAP PERTUMBUHAN SEMAI CENDANA (Santalum album L.) - Muhammad Kasim; Lenny M. Mooy (Politeknik Pertanian Negeri Kupang, 2023)
The problem faced in sandalwood cultivation is the difficulty of obtaining good quality seeds. The porpuse of the research is to know the influence of give Fertilizer dose NPK about the growth of seed sandalwood with the combination of the hosts plant. The research that had been in the district Naikolan subdistrict Maulafa Kupang from May until September 2019. This study used the Group Randomized Design method (RAK) with the 5 treatment and the 5 repeat. The treatment that used to give dose manure NPK consist of control (P0); 2 g/1 kg tanah (P1); 4 g/1 kg tanah (P2); 6 g/1 kg tanah (P3); and 8 g/1 kg tanah mediteran / (P4). The results showed that the treatment dose of NPK 8 g/1 kg tanah fertilizer gave the highest yield of sandalwood seedlings compared to other treatments on the parameters of the number of houstorium, seedling height, number of leaves, stem diameter and dry weight of seedlings. Keywords: sandalwood, growth, hosts plant, NPK fertilizer